Against the grain : - Stern, Joel M. (John Wiley & Sons, Inc., 2003)
In Against the Grain, Joel Stern shares for the first time, not only the story of how EVA swept the corporate world, but the story behind the story-the intellectual underpinnings of EVA, how he and his colleagues at Stern Stewart & Co. promoted the concept, won its initial acceptance by major corporations, and later turned the concept into a revolution. He has for good reason been called a one-man catalyst for change. In an engaging memoir, he has given us not only an account of his business strategy, but also provided fascinating anecdotes and vignettes of encounters with leading businessmen on four continents.